Comparative genome-wide association study shows single-nucleotide polymorphic loci associated with resistance to Meloidogyne incognita, Fusarium oxysporum f. sp. phaseoli, and their co-infection in common bean - Maria Laura Urbano Nascimento; César Júnior Bueno; Carlos Eduardo Rossi; Antônio Augusto Franco Garcia; Maria Lúcia Carneiro Vieira; Luís Eduardo Aranha Camargo; Alisson Fernando Chiorato; Sérgio Augusto Morais Carbonell; Monica Rodriguez; Luciana Lasry Benchimol-Reis (Planta, 2026)
Main conclusion The genetic architecture underlying co-infection with Meloidogyne incognita and Fusarium oxysporum f. sp. phaseoli differs from that observed when these pathogens are evaluated individually. Abstract Common bean ( Phaseolus vulgaris L.) yield is threatened by simultaneous infection with the root-knot nematode Meloidogyne incognita (Mi) and Fusarium oxysporum f. sp. phaseoli (Fop). Root-knot nematodes are believed to intensify the severity of Fusarium wilt in common bean, and specific genomic regions are understood to be associated with the host response, whether conferring susceptibility or resistance. To elucidate the genetic mechanisms of this interaction, phenotypic traits were evaluated in greenhouse trials, followed by associative mapping using a genome-wide association study (GWAS) approach. The plant material consisted of a core collection of 180 common bean genotypes from the Agronomic Institute (IAC, Campinas, Brazil) diversity panel. The effects of Fop and Mi were evaluated individually and in co-infection. Associative mapping was performed using the Bayesian information and linkage disequilibrium iteratively nested keyway (BLINK) model. When plants were infected with Mi, significant SNPs were detected on chromosomes Pv07, Pv08, and Pv10 based on gall counts. SNPs were detected on Pv05, Pv06, P10, and Pv11 in association with co-infection. Regions associated with egg mass count were detected on Pv02, Pv04, and Pv05. However, co-infection revealed SNPs on chromosomes P10 and Pv11. Three SNPs were associated with Fusarium wilt–two on Pv07 and one on Pv08. The genomic regions and markers associated with resistance to Mi and Fop provide new resources for advancing understanding of host–pathogen relationships in these important pathosystems.